The THE INFLUENCE OF MOTIVATION AND WORK ENVIRONMENT ON THE PERFORMANCE OF EMPLOYEES OF THE REGIONAL DISASTER MANAGEMENT AGENCY IN SOLOK DISTRICT - Nurhayati, Nurhayati; Nirwana, Ida; Kurniawan, Dutanof (Jurnal Manajemen, 2024)
This study was conducted on employees of the Regional Disaster Management Agency (BPBD) of Solok Regency. The purpose of this study was to determine whether there was a relationship between Motivation and Work Environment on Employee Performance at the Regional Disaster Management Agency (BPBD) of Solok Regency. With a sample of 53 respondents studied using the total sampling method. Based on the results of statistical analysis, it can be interpreted that Motivation partially has a significant effect on Employee Performance, this is evidenced by the t test with a significant value of t count 6.255> t table 1.990 in the significance level value, 0.000 <0.05. So it can be interpreted that Motivation has a significant effect on Employee Performance. Based on the results of statistical analysis, it can be concluded that the Work Environment partially has a significant effect on Employee Performance, this is evidenced by the t test with a significant value of t count 7.133> t table 1.990 and a significance level value of 0.000 <0.05, so it can be concluded that the Work Environment has a significant effect on Employee Performance. It can be concluded that simultaneously Motivation and Work Environment have a significant effect on the Performance of Employees of the Regional Disaster Management Agency (BPBD) of Solok Regency. This is proven by using the F test with a significant value of f count 57.434> f table 3.11 and the significant value produced is 0.000 and this value is much smaller than a (0.05). This can also be seen from the R Square value obtained 0.590 or 59% and the remaining 41% is influenced by other variables not included in this study. Keywords: Motivation; Work Environment; Employee Performance